Online car mechanic shop system - Wong, Sai Kit (2020)
Today, every family must have a car and will send their car for repair or regular service. However, one of the mechanic shops in Simpang Pulai, Perak, Malaysia named Pusat Servis Tayar Dan Kereta Maeng Wa still operate their business in a manual way. The shop only accepts walk-in customers, put service reminder sticker on the car windscreen to remind customers for next service due, and accept outdoor service requests by customers through phone calling. As a result, this has affected both car mechanic shop and customers. Firstly, walk-in customers may leave due to long waiting time and thus the shop lost its profits. Secondly, customer perform regular car service lately due to faded or dropped service reminder sticker and thus shop lost its profits again. Thirdly, customers need to wait longer time of the arrival of the shop for outdoor service due to the shop may not familiar of the location or the location stated by customers though phone calling is not clear. Therefore, this final year project aims to deliver an online system for the shop and its customers. Front-end mobile applications developed in Android platform and supported by back-end Amazon Web Service Elastic Compute Cloud (AWS EC2) server will be used by customers and the clerk of the shop. Ultimately, the main solutions provided by this system are service booking, service reminder, and car breakdown assistant.